The record of the typothere Pachyrukhos (Mammalia, Notoungulata) and the Chinchillid Prolagostomus (Mammalia, Rodentia) in the Santa Cruz Formation (early–middle Miocene) south to the Río Coyle, Patagonia, Argentina - Vizcaíno, Sergio Fabián (2021)
The continental early–middle Miocene Santa Cruz Formation (SCF) from Patagonia is one of the most important stratigraphic units of southern South America in terms of the terrestrial Neogene record. Its fossil content was pivotal for establishing the succession of Cenozoic faunas from Patagonia and formed the basis of the Santacrucian South American Land Mammal Age. Despite the updated knowledge recently achieved, the stratigraphic distribution of many taxa within the SCF remains to be clarified. That is the case with the typothere notoungulate Pachyrukhos and the chinchillid rodent Prolagostomus. New information on the stratigraphy of the SCF along the north bank of the Río Gallegos and Cabo Buen Tiempo (Santa Cruz Province), together with a detailed analysis of the provenance information of the specimens in the principal old museum collections, sheds light on the record of these taxa south to Río Coyle. Our results show that the first recorded occurrence of both taxa in the area was between ~17 Ma and 17.41 Ma, restricted to the upper part of the SCF, including the upper part of the Estancia La Costa Member at Cañadón Las Totoras-Monte Tigre, and the superimposed Estancia La Angelina Member along the Río Gallegos and Cabo Buen Tiempo. Their presence suggests a trend to aridification in the upper part of the SCF south to the Río Coyle. These results are consistent with recent information obtained from other locations of the SCF north to the Río Coyle.